Comportamento alimentar e estratégias de enfrentamento em mulheres submetidas à cirurgia bariátrica - AQUINO, Samily Natania Alves Meireles (2021)
Obesity is a complex condition that affects all ages and social classes and is one of the main public health problems today. Bariatric surgery is the most recommended treatment for grade III obesity because it is more effective in weight loss and reduces the number of comorbidities associated with obesity. The post-surgical period involves strategies to deal with the demands, limitations, and changes in habits and lifestyle inherent to the weight loss process, strategies that are related to the potential success of the treatment and the maintenance of the benefits obtained with the surgery. The aim of this study is to investigate the eating behavior and coping strategies in women undergoing bariatric surgery. To achieve this objective, 25 women answered four instruments: Sociodemographic Questionnaire, Semi-structured Interview Script, Three Factor Eating Questionnaire (TFEQ-R21) and the Problem Coping Modes Scale (EMEP). For the quantitative analysis, the Statistical Package for Social Science program (version 24.0) was used, in which descriptive and correlational statistical analyses were performed. For the qualitative analysis, the content analysis proposed by Minayo (2013) was employed. The results indicated that the average age of the participants is 43 years, in which 36% were single, 84% reported having children, 56% had some professional activity, 40% have an income of one minimum wage and 44% reported having completed high school. Regarding the clinical and treatment history, 32% of the sample had undergone bariatric surgery in the period of six months to one year, 76% had undergone gastric sleeve technique, 64% had psychological counseling before surgery and 56% continued in the psychological follow-up after surgery. About the relationship with food, significant changes with the surgery and predominance of food restriction, presence of feelings such as fear and guilt related to the act of eating were noted. Regarding the dimensions of eating behavior assessed by the TFEQ-R21, the results also pointed to higher levels of cognitive restriction eating behavior corresponding to 56.77% of the sample, and the coping strategy focused on the problem was the most expressive in the sample, comprising 75.24% of the interviewees. Regarding the correlational data, the indicator “problem-focused coping” correlated negatively with “emotional eating” (ρ = -.525; p = .007) and “eating discontrol” (ρ = -.582; p = .002), and the indicator “emotion focused coping” correlated positively with “emotional eating” (ρ = .420; p = .037) and “eating discontrol” (ρ = .549; p = .004). The importance of multiprofessional support and the contributions of psychology in assisting the development of adaptive coping strategies and support for these women in the post-surgical period is highlighted, contributing to the promotion of health and quality of life after surgery.